Training workshops on Participatory Integrated Climate Services for Agriculture (PICSA) - Dembélé, Catherine; Bazie, Paulin (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA) is a new initiative that seeks to enhance access to climate information services and validated climate-smart agriculture technologies in Africa. It is a 3-year project funded by the World Bank and implemented in 6 African countries including 3 countries in West Africa (Ghana, Mali, and Senegal). The Project aims to strengthen the capacity of targeted CCAFS (CGIAR Research Program on Climate Change, Agriculture and Food Security) partners and stakeholders, and to enhance access to climate information services and validated climate-smart agriculture technologies in the eligible countries in Africa. With the support of AICCRA projects, farmers and livestock keepers would be able to better anticipate climate-related events and take preventative actions, with better access to climate advisories linked to information about effective response measures. This would help communities better safeguard their livelihoods and the environment. The project has 3 main components including (1) Knowledge Generation and Sharing, (2) Strengthening Partnerships for Delivery, and (3) Validating Climate-Smart Agriculture Innovations through Piloting. In Ghana, AICCRA is implemented by various CGIAR institutions and NGOs led by the International Institute for Tropical Agriculture (IITA) Benin. As climate information is key in the process, in collaboration with IITA, the World Agroforestry (ICRAF/SAHEL) has organized a training of trainers in Kumasi for field agents involved in the implementation of the project in Ghana to understanding and implementing the Participatory and Integrated Climate Services for Agriculture (PICSA) approach. Developed by the University of Reading in the framework of CCAFS project, PICSA has been taken to scale and adapted widely in West Africa by ICRAF/SAHEL since 2015. PICSA is an approach that has been developed for extension agents to enable them to improve the support provided to farmers considering climate information relevant to the locality of the farmers. PICSA goes beyond climate prediction, because in the approach farmers begin long before the start of the season exploring several options based on historical climate information for their locality. This involves using participatory planning tools to help farmers making adequate decisions based on precise climate and meteorological information specific to their localities and options for agriculture, livestock/ fishery production and other locally relevant livelihood options. The training had taken place from June 14 to 18.